2021
DOI: 10.21203/rs.3.rs-998151/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Circulating Cell Free DNA and Citrullinated Histone H3 As Useful Biomarkers of NETosis In Endometrial Cancer.

Abstract: Background. Cancer mortality is mainly caused by organ failure and thrombotic events. It has been demonstrated that NETosis, a chromatin release mechanism implemented by neutrophils, may contribute to these lethal systemic effects. Our aim was to investigate NETosis biomarkers in endometrial cancer (EC).Methods. The experiments were conducted on 21 healthy subject (HS) with no gynecological conditions, and on 63 EC patients. To assess the presence of NETosis features IHC and IF was performed using antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Our results showed that most NET formation pathway genes were down‐regulated after treatment. Among them, CitH3, a maker of NETosis (Ronchetti et al, 2022), was highly down‐regulated in fluctuating sites, but no differences were observed in the progressing samples. NETosis can be activated by a variety of receptors, all of which were down‐regulated in both progressing and fluctuating samples.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that most NET formation pathway genes were down‐regulated after treatment. Among them, CitH3, a maker of NETosis (Ronchetti et al, 2022), was highly down‐regulated in fluctuating sites, but no differences were observed in the progressing samples. NETosis can be activated by a variety of receptors, all of which were down‐regulated in both progressing and fluctuating samples.…”
Section: Discussionmentioning
confidence: 99%